Prevalence of myopia and binocular vision dysfunctions in microscopists - Rajeshwori Ngakhushi (Guoji Yanke Zazhi, 2018)
AIM: To determine the refractive and binocular vision status in clinical microscopists. METHODS: It was an observational and cross sectional hospital based study. One hundred and three microscopists working at Tribhuvan University Teaching Hospital were recruited in the study. All subjects had a comprehensive eye examination including static retinoscopy, dynamic retinoscopy and orthoptic evaluation. Information about their visual symptoms associated with microscopy was also collected. RESULTS: The prevalence of refractive error in this group of microscopists was 69.90%. Majority of the subjects were myopic(68.93% of total subjects)with the mean myopic error of -1.58±1.89 D. Convergence insufficiency was found in 61.20% of the study population. Prevalence of accommodative insufficiency and infacility were 41.30% and 40.06% respectively. Fusional vergence was also reduced in this study population. The outcomes of this study were expected to increase the awareness about the refractive and binocular vision anomalies among this population. CONCLUSION: There was found to be increased prevalence of refractive error in clinical microscopists, especially myopia. Majority of them had vergence and accommodative anomalies. Most of the subjects reported asthenopic symptoms associated with their microscopy work, which may affect their work efficiency.